An integrated approach to assess the dynamics of a peri-urban watershed influenced by wastewater irrigation - Jampani, Mahesh; Amerasinghe, Priyanie H.; Pavelic, Paul (Elsevier, 2015)
In many urban and peri-urban areas of India, wastewater is under-recognized as a major water resource. Wastewater irrigated agriculture provides direct benefits for the livelihoods and food security of many smallholder farmers. A rapidly urbanizing peri-urban micro-watershed (270 ha) in Hyderabad was assessed over a 10-year period from 2000 to 2010 for changes in land use and associated farming practices, farmer perceptions, socio-economic evaluation, land-use suitability for agriculture and challenges in potential irrigated area development towards wastewater use. This integrated approach showed that the change in the total irrigated area was marginal over the decade, whereas the built-up area within the watershed boundaries doubled and there was a distinct shift in cropping patterns from paddy rice to paragrass and leafy vegetables. Local irrigation supplies were sourced mainly from canal supplies, which accounted for three-quarters of the water used and was largely derived from wastewater. The remainder was groundwater from shallow hard-rock aquifers. Farmer perception was that the high nutrient content of the wastewater was of value, although they were also interested to pay modest amounts for additional pre-treatment. The shift in land use towards paragrass and leafy vegetables was attributed to increased profitability due to the high urban demand. The unutilised scrubland within the watershed has the potential for irrigation development, but the major constraints appear to be unavailability of labour and high land values rather than water availability. The study provides evidence to support the view that the opportunistic use of wastewater and irrigation practices, in general, will continue even under highly evolving peri-urban conditions, to meet the livelihood needs of the poor driven by market demands, as urban sprawl expands into cultivable rural hinterlands. Policy support is needed for enhanced recognition of wastewater for agriculture, with flow-on benefits including improved public health and protection of ecosystem services.